Popular politics and the path to durable democracy - Kadivar, Mohammad Ali 1983- (Princeton, New Jersey: Princeton University Press, 2022)
"A groundbreaking account of how prolonged grassroots mobilization lays the foundations for durable democratizationWhen protest swept through the Middle East at the height of the Arab Spring, the world appeared to be on the verge of a wave of democratization. Yet with the failure of many of these uprisings, it has become clearer than ever that the path to democracy is strewn with obstacles. Mohammad Ali Kadivar examines the conditions leading to the success or failure of democratization, shedding vital new light on how prodemocracy mobilization affects the fate of new democracies.Drawing on a wealth of new evidence, Kadivar shows how the longest episodes of prodemocracy protest give rise to the most durable new democracies. He analyzes more than one hundred democratic transitions in eighty countries between 1950 and 2010, showing how more robust democracies emerge from lengthier periods of unarmed mobilization. Kadivar then analyzes five case studies-South Africa, Poland, Pakistan, Egypt, and Tunisia-to investigate the underlying mechanisms. He finds that organization building during the years of struggle develops the leadership needed for lasting democratization and strengthens post-dictatorship civil society.Popular Politics and the Path to Durable Democracy challenges the prevailing wisdom in American foreign policy that democratization can be achieved through military or coercive interventions, revealing how lasting change arises from sustained, nonviolent grassroots mobilization"--
"This book will examine the conditions that lead to either the survival or failure of new democracies, showing how pro-democracy mobilization affects the fate of new democracies. Mohammad Ali Kadivar argues that the longest episodes of prodemocracy protest lead to the most durable new democracies, because social movements had to develop an organization infrastructure to mobilize over a long period of time, providing leadership for democratization and democratic governance. Kadivar draws on an original dataset of all 112 democratic transitions, in 80 countries, between 1950 and 2010. He assesses the length and scale of pro-democracy protests and whether armed or unarmed mobilization played a role in the transition. This dataset shows that after accounting for relevant socioeconomic characteristics, more robust democracies emerge from longer episodes of unarmed mobilization. The book will also comparatively analyze five case studies-South Africa, Poland, Pakistan, Egypt, and Tunisia-to investigate the underlying mechanisms and alternatives to the book's central argument, as well as use primary material in Arabic for the case studies of Egypt and Tunisia. Popular Politics and the Path to Durable Democracy will make a theoretical contribution to the study of democratization, social movements, and society. While other major studies of democratic survival focus on economic development, international context, and institutional design and ignore that democracy is built through different pathways and that these pathways make a mark of democratic trajectory, this book will make a novel contribution to the field by showing how sustained unarmed mobilization forges durable democracies"--
Introduction -- Contentious mobilization, and democratic outcomes in a cross national perspective -- Mechanisms of success and failure in South Africa, Poland, and Pakistan -- Predicaments of rapid success : Egypt's failed democratization 2011-13 -- The anomalous case of Tunisia -- Conclusion.
Includes bibliographical references and index.
Keywords: New democracies; Democracy; Political Science; Democratization; Social movements -- Political aspects; World politics -- 1945-1989.; World politics -- 1989-; POLITICAL SCIENCE / Political Ideologies / Democracy; POLITICAL SCIENCE / International Relations / General